Determinantes sociais da saúde e desmame precoce em Domingos Martins, Espírito Santo - Lutzke, Camila Lampier (2021)
Introduction Despite being a health behavior with numerous short and long-term benefits for both mother and baby, breastfeeding is still hampered by numerous factors. Pomeranian culture is strong and very peculiar, and must be understood in its interference in the health-disease process. Objectives: To evaluate the association between social determinants of health and early weaning of children from a rural community in Espírito Santo from the perspective of local culture. Methodology: Quantitative and cross-sectional study, carried out with 143 medical records of children attended in childcare consultations in the District of Melgaço, Domingos Martins, Espírito Santo. The medical records contained socioeconomic, maternal, breastfeeding and child care data. Results: The prevalence of early weaning in the studied sample was 66.4%. Pacifier use and bottle feeding were positively correlated with early weaning. Conclusion: the high prevalence of early weaning indicates the need for further studies to fully understand the role of the Pomeranian culture on the health of the population.